Library Management Strategies in Meeting The Information Needs Of Library Users at Balai Bahasa Sumatera Utara - Hasibuan, Ramadani Syafitri; Batubara, Abdul Karim (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Purpose Research. This study examines the strategies of library managers at the North Sumatra Language Center Library in meeting users' information needs. The research highlights the importance of adapting library services to technological developments and the unique role of special libraries in supporting linguistic and literary research. Research Method. Using a qualitative descriptive approach, data were collected through observation, interviews, and literature review, then analyzed inductively with the Miles and Huberman model to identify strategies and challenges in library management. Analysis Data. The results of the analysis show that library managers utilize linguistic and literary collections, initiate digitization efforts, apply information technology, and promote information literacy to improve accessibility and service effectiveness. Results. The study also identifies several obstacles, including limited funding, insufficient infrastructure, and the need for ongoing staff development, that hinder service optimization. Conclusions. The findings indicate that the library has taken initial steps toward modernization by integrating traditional and digital resources. Stronger institutional support, technological infrastructure, and librarian competency development are required to maximize its role as a specialized information center. The results are expected to serve as a reference for other special libraries and contribute to the advancement of information literacy and linguistic research at the regional level. Keywords: Library Management; Information Needs; Special Library; Information Literacy; Qualitative Research